2007
DOI: 10.1016/j.physbeh.2007.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Hypoglycemia activates arousal-related neurons and increases wake time in adult rats

Abstract: Hypoglycemia resulting from excess of exogenous or endogenous insulin elicits central nervous system activation that contributes to counterregulatory hormone secretion. In adult humans without diabetes, hypoglycemia occurring during sleep usually produces cortical activation with awakening. However, in adult humans with type 1 diabetes, hypoglycemic arousal appears blunted or absent. We hypothesized that insulin injection sufficient to produce hypoglycemia would induce awakening in adult male rats. Polysomnogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 52 publications
1
7
0
Order By: Relevance
“…However, it is expressed at moderate levels in hypothalamic nuclei such as the dorsomedial hypothalamus (DMH) and lateral hypothalamic area (LHA), which are known to be important for energy homeostasis, and which are also targets of ARC and VMH projections. Interestingly, TCF7L2 is also moderately expressed in the basal forebrain, a region that has long been the focus of sleep research, but which recently has also been shown to be responsive to hypoglycemia (Cai et al, 2001; Tkacs et al, 2007). …”
Section: Discussionmentioning
confidence: 99%
“…However, it is expressed at moderate levels in hypothalamic nuclei such as the dorsomedial hypothalamus (DMH) and lateral hypothalamic area (LHA), which are known to be important for energy homeostasis, and which are also targets of ARC and VMH projections. Interestingly, TCF7L2 is also moderately expressed in the basal forebrain, a region that has long been the focus of sleep research, but which recently has also been shown to be responsive to hypoglycemia (Cai et al, 2001; Tkacs et al, 2007). …”
Section: Discussionmentioning
confidence: 99%
“…However, it is expressed at moderate levels in hypothalamic nuclei such as the dorsomedial hypothalamus (DMH) and lateral hypothalamic area (LHA), which are known to be important for energy homeostasis, and which are also targets of ARC and VMH projections. Interestingly, TCF7L2 is also moderately expressed in the basal forebrain, a region that has long been the focus of sleep research, but which recently has also been shown to be responsive to hypoglycemia (Cai et al,2001; Tkacs et al,2007).…”
Section: Discussionmentioning
confidence: 99%
“…Studies using neurotropic viruses have shown that in the perifornical hypothalamus only orexin- and MCH-containing neurons project to adrenal sympathetic premotor neurons in the RVLM (Kerman et al, 2007 ). In addition, insulin-induced hypoglycemia or neuroglucoprivation induces Fos expression in orexin neurons of the PeH suggesting a possible role in glucose sensing (Moriguchi et al, 1999 ; Briski and Sylvester, 2001 ; Cai et al, 2001 ; Paranjape et al, 2006 ; Tkacs et al, 2007 ). On the other hand, an in vitro study has shown that GI orexin neurons respond in an identical fashion to both glucose and 2DG through a K + channel-mediated mechanism.…”
Section: Neural Circuitry Involved In the Glucose Counterregulatory Rmentioning
confidence: 99%